A fully automatic system to assess foot collapse on lateral weight-bearing foot radiographs: A pilot study. (January 2022) - Lauder, J.; Harris, J.; Layton, B.; Heire, P.; Sorani, A.; DeSancha, M.; Davison, A.K.; Sammut-Powell, C.; Lindner, C.
Highlights: Clinical decision support system to automatically assess radiographic changes in foot collapse. Fully automatic generation of Meary's angle, calcaneal tilt, and cuboid height. Good manual measurement agreement among clinical experts for all three measurements. Automatically generated measurements in agreement with clinical expert measurements. First software system to automatically generate measurements in acquired foot collapse. Abstract: Background: Foot collapse is primarily diagnosed and monitored using lateral weight-bearing foot x-ray images. There are several well-validated measurements which aid assessment. However, these are subject to inter- and intra-user variability. Objective: To develop and validate a software system for the fully automatic assessment of radiographic changes associated with foot collapse; automatically generating measurements for calcaneal tilt, cuboid height and Meary's angle. Methods: This retrospective study was approved by the Health Research Authority (IRAS 244852). The system was developed using lateral weight-bearing foot x-ray images, and evaluated against manual measurements from five clinical experts. The system has two main components: (i) a Random Forest-based point-finder to outline the bones of interest; and (ii) a geometry-calculator to generate the measurements based on the point positions from the point-finder. The performance of the point-finder was assessed using the point-to-point error (i.e. the mean absolute distance between each found point and the equivalent ground truth point, averaged over all points per image). For assessing the performance of the geometry-calculator, linear mixed models were fitted to estimate clinical inter-observer agreement and to compare the performance of the software system to that of the clinical experts. Results: A total of 200 images were collected from 79 subjects (mean age: 56.4 years ±12.9 SD, 30/49 females/males). There was good agreement among all clinical experts with intraclass correlation estimates between 0.78 and 0.86. The point-finder achieved a median point-to-point error of 2.2 mm. There was no significant difference between the clinical and automatically generated measurements using the point-finder points, suggesting that the fully automatically obtained measurements are in agreement with the manually obtained measurements. Conclusions: The proposed system can be used to support and automate radiographic image assessment for diagnosing and managing foot collapse, saving clinician time, and improving patient outcomes.